Khảo sát ảnh hưởng của một số chất xúc tác amin họ imidazol đến quá trình đóng rắn của dầu lanh epoxy hóa bằng anhydrit 4-metylhexahydrophtalic. Phần 1. Khảo sát ảnh hưởng của imidazol và 2-metylimidazol đến quá trình đóng rắn của dầu lanh epoxy hóa bằng - Tuấn, Phạm Anh; Diệu, Trần Vĩnh; Phúc, Bạch Trọng; Hường, Hà Thu (Vietnam Journal of Chemistry, 2014)
In this study, the process of curing epoxidized linseed oil (ELO) with 4-methylhaxahydrophtalic anhydride system (MHHPA) in the presence of 2-methylimidazole (2-MI) and Imidazole (IM) has been investigated. The change of temperature vs. curing time was carried out in thermal measuring instrument. Gel content was determined by method of acetone extraction on Soxhlet instruments and Origin Software Version 9.0 was used to survey the curing process. The results show that, two kinds of above catalysts could trongly promote for the curing process of ELO and MHHPA. In which, with the rising catalyst contents, the time to reach the maximum temperature of exothermic decreased and the curing degree and curing rate of bioepoxyresin system increased. Keywords: Epoxidized linseed oil, bio epoxy resin.